Outcomes From the Multicenter Italian Registry on Primary Endovascular Treatment of Aortoiliac Occlusive Disease. (October 2019) - Piffaretti, Gabriele; Fargion, Aaron Thomas; Dorigo, Walter; Pulli, Raffaele; Gattuso, Andrea; Bush, Ruth L.; Pratesi, Carlo
Purpose: To report the results of endovascular treatment of iliac and complex aortoiliac occlusive disease (AIOD) in a multicenter Italian registry.Materials and Methods: A retrospective, multicenter, observational cohort study analyzed 713 patients (mean age 68±10 years; 539 men) with isolated iliac and complex aortoiliac lesions treated with primary stenting between January 2015 and December 2017. Indications for treatment were claudication in 406 (57%) patients and critical limb ischemia in 307 (43%). According to the TransAtlantic Inter-Society Consensus II (TASC) classification, the lesions were categorized as type A (104, 15%), type B (171, 24%), type C (170, 24%), and type D (268, 37%). Early (<30 days) endpoints included mortality, thrombosis, and major complications. Late major outcomes were primary and secondary patency and freedom from reintervention as estimated by Kaplan-Meier analysis; estimates are given with the 95% confidence intervals (CIs). Associations between baseline variables and primary patency were sought with multivariate analysis; the results are presented as the hazard ratio (HR) and 95% CI.Results: Technical success was achieved in 708 (99%) lesions; in-hospital mortality was 0.6% (n=4). The median follow-up was 11 months (range 0–42). The estimated primary patency rate was 96% (95% CI 94% to 97%) at 1 year and 94% (95% CI 91% to 96%) at 2 years. The estimated secondary patency was 99% (95% CI 97% to 99%) at 1 year and 98% (95% CI 95% to 99%) at 2 years. The estimated freedom from reintervention was 98% (95% CI 96% to 99%) at 1 year and 97% (95% CI 94% to 98.5%) at 2 years. Cox regression analysis demonstrated that the application of a covered stent was associated with an increased need for reintervention (HR 1.4, 95% CI 1.10 to 1.74, p=0.005). Chronic obstructive pulmonary disease was associated with decreased primary patency (HR 3.7, 95% CI 1.25 to 10.8, p=0.018).Conclusion: Endovascular intervention with primary stent placement for aortoiliac occlusive disease achieved satisfactory 2-year patency regardless of the complexity of the lesion. Almost all TASC lesions should be considered for primary endovascular intervention if suitable.